On the thermoelastic functionally graded material of ceramic-metal plate - Bayat, Mehdi; Hamouda, Abdel Magid Salem; Mahdi , E. (Universiti Putra Malaysia Press, 2005)
This paper is devoted to review the current status related to thermoelastic functionally graded material (FGM) of plate. Laminated composite plates are extensively used due to their high specific strength and high specific stiffness. However, the abrupt change in material properties across an interface between discrete materials introduces large interlaminar stresses that could cause delamination. One way to overcome this adverse effect is to use functionally graded materials (FGMs). In a functionally graded (FG) plate, the volume fraction of the constituent materials changes gradually, usually in the thickness direction only. FGMs have been developed as a new material that is adaptable for a super-high-temperature (temperature gradient less than -10°C and more than 2000°C when time and thickness are small) environment and have come to international attention. Therefore, the thermoelastic problems of FGM become important. This paper reviews papers related to FGM published in the literature on thermoelastic of Ceramic-metal Plate.